Perancangan Aplikasi Peminjaman Buku Perpustakaan Pada SDN Mekarjaya 11 Depok - Thasia Anjani; Za'imatun Niswati; Intan Mutia (Universitas Indraprasta PGRI Jakarta, 2020)
The book lending application at SDN Mekarjaya 11 is still manually, so the recording of loans and repayments is inaccurate. The purpose of this study is to facilitate library employees in recording the book process such as borrowing, repayment, fines and reports of the whole process. The author uses the Research and Development method, in general is the development and research in the field of technology. This library application using the Java language also uses Netbeans IDE, Xampp and MySQL software. The result of this design is the library application of SDN Mekarjaya 11 which facilitates employee performance in the book lending data collection process.